Pagar Laut sebagai Instrumen Pertahanan Negara dalam Bingkai Wawasan Nusantara - Dwi Vivi Lestiani; Aisyah Berlian Dian; Irma Hidayatul Saputri (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This article discusses the role of sea fences as an instrument of national defense within the framework of the Archipelago Outlook. Sea fences are seen as a strategic line of defense against various threats in Indonesia's maritime territory. With a descriptive-qualitative approach and secondary data from online news, this article reviews the function of sea fences in strengthening the sovereignty and unity of the country's territory. The findings show that sea fences are not only physical, but also geopolitical symbols that internalize the values ​​of Pancasila and the 1945 Constitution.